2010
DOI: 10.1097/sla.0b013e3181d3d21f
|View full text |Cite
|
Sign up to set email alerts
|

Gut Hypertrophy After Gastric Bypass Is Associated With Increased Glucagon-Like Peptide 2 and Intestinal Crypt Cell Proliferation

Abstract: RYGB leads to increased GLP-2 and mucosal crypt cell proliferation. Other gut hormones from l-cells remain elevated for at least 2 years in humans. These findings may account for the restoration of the absorptive surface area of the gut, which limits malabsorption and contributes to the long-term weight loss after RYGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
124
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(141 citation statements)
references
References 39 publications
11
124
0
2
Order By: Relevance
“…35 The gut is metabolically very active and gut hypertrophy may hence explain a higher energy requirement that contributes to body weight loss. 9,37,38 These findings are in line with previous reports demonstrating a reduced body weight without decreased food intake or malabsorption, but increased energy expenditure after GBP in rats. 39,40 Furthermore, Stylopoulos et al 41 described a 19% increase in total and a 31% increase in resting energy expenditure in rats after GBP operation.…”
Section: Experimental Datasupporting
confidence: 83%
“…35 The gut is metabolically very active and gut hypertrophy may hence explain a higher energy requirement that contributes to body weight loss. 9,37,38 These findings are in line with previous reports demonstrating a reduced body weight without decreased food intake or malabsorption, but increased energy expenditure after GBP in rats. 39,40 Furthermore, Stylopoulos et al 41 described a 19% increase in total and a 31% increase in resting energy expenditure in rats after GBP operation.…”
Section: Experimental Datasupporting
confidence: 83%
“…Glucagon is counter-regulatory to insulin action, increasing glucose output and inhibiting glucose uptake in the liver, and it has been linked to insulin resistance in obese subjects with normal or impaired glucose tolerance (Ahrén 2006, Weiss et al 2011. However, this appears unlikely because bariatric surgery, particularly Roux-en-Y gastric bypass (RYGB) (Saeidi et al 2013), which is the most effective therapy for obesity and T2D (Carlsson et al 2012, Cummings 2012, increases blood GLP2 (by 200%) at postprandial status (le Roux et al 2010). Bariatric surgery normalizes blood glucose concentrations in the majority of T2D humans independent of weight loss (Mingrone et al 2012, Schauer et al 2012) and can induce diabetes remission up to 6 years (Cohen et al 2012).…”
Section: Glp2 and Glycaemic Controlmentioning
confidence: 99%
“…4 The first mechanisms have been shown to be at least partly physiologically induced by alterations in gastrointestinal and central neuroendocrine signalling. [5][6][7][8] The postprandial responses of the gut hormones glucagonlike peptide-1 (GLP-1) and peptide YY3-36 (PYY), which are produced from the L cells in the gut, are increased after gastric bypass. [6][7][8] We and others have demonstrated in a rodent model that these anorexigenic gut hormones reduce hunger and induce satiety in a dose-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] The postprandial responses of the gut hormones glucagonlike peptide-1 (GLP-1) and peptide YY3-36 (PYY), which are produced from the L cells in the gut, are increased after gastric bypass. [6][7][8] We and others have demonstrated in a rodent model that these anorexigenic gut hormones reduce hunger and induce satiety in a dose-dependent manner. 9,10 We have also found that patients with suboptimal body weight (BW) loss after gastric bypass had attenuated postprandial PYY and GLP-1 responses.…”
Section: Introductionmentioning
confidence: 99%